Advances and Perspective on Antimicrobial Nanomaterials for Biomedical Applications - Garg, Preeti; Attri, Prerna; Sharma, Rohit; Chauhan, Moondeep; Chaudhary, Ganga Ram (Frontiers in Nanotechnology, 2022)
Microbial infection and antibiotic resistance is recognized as a serious problem to society from both an economical perspective and a health concern. To tackle this problem, “nanotechnology,” a multidisciplinary field of research, has provided a plethora of nanomaterials for potential applications in the antimicrobial sector. This letter discusses how antimicrobial nanomaterials are shaping this challenging field and being evaluated as therapeutic and medication delivery agents. The recently designed smart antimicrobial surfaces with switchable features that displayed synergistic antibacterial action were also highlighted. To end, we provide the current scenario and future perspectives with regards to emerging antimicrobial nano-engineered materials and nanotechnology